Pulmonary physiology in clinical practice - Martin, L.
Web version of the book. Content: Title Page Table of Contents Chapter 1: Clinical Approach Chapter 2: Structure and Function Chapter 3: Lung Mechanics Chapter 4: PCO2 and Alveolar Ventilation Chapter 5: Oxygen Transfer Chapter 6: Is the Patient Adequately Oxygenated Chapter 7: Acid-Base Balance Chapter 8: Pulmonary Circulation Chapter 9: Oxygen Therapy Chapter 10: Mechanical Ventilation Chapter 11: Respiratory Failure Chapter 12: Exercise Physiology Chapter 13: Pleural Effusions Chapter 14: Sleep Disorders